A Study of Language and Identity as Neocolonial Means in Firoozeh Dumas’ Funny in Farsi - Hamed Rezaeinejad; Samira Sasani (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
The phenomenon of migration, whether by choice or necessity, has shaped various spheres, giving rise to a corpus referred to as migrant literature. Many authors of this genre explore the sociopolitical contrasts between their current and native lands, sharing their experiences while sometimes allegedly concealing some aspects of the immigration process. This has sparked contentious debates that extend beyond the literary realm. Firoozeh Dumas’ well-known memoir, Funny in Farsi, humorously portrays the Iranian-American family’s journey through cultural disparities. In an attempt to reappraise this light-hearted approach to Dumas’ work, this research utilizes Ngugi wa Thiong’o’s language studies and Milton Gordon’s analysis of identity in diaspora. This study concludes that the Englishness of Dumas’ memoir and its narrative’s normalization of assimilation in the host country, align with the neo-colonial politics of the West theorized by Kwame Nkrumah. These neo-colonial dynamics of power in turn can potentially disrupt the ongoing decolonization process.